Team of rivals : the political genius of Abraham Lincoln - Goodwin, Doris Kearns (New York : Simon & Schuster, 2005)
This multiple biography is centered on Lincoln's mastery of men and how it shaped the most significant presidency in the nation's history. Historian Goodwin illuminates Lincoln's political genius, as the one-term congressman rises from obscurity to prevail over three gifted rivals to become president. When Lincoln emerged as the victor at the Republican National Convention, his rivals were dismayed. Throughout the turbulent 1850s, each had energetically sought the presidency as the conflict over slavery led inexorably to civil war. That Lincoln succeeded, Goodwin demonstrates, was because of his extraordinary ability to put himself in the place of other men, to experience what they were feeling, to understand their motives and desires. It was this that enabled Lincoln to bring his disgruntled opponents together, create the most unusual cabinet in history, and marshal their talents to the task of preserving the Union.
pt. 1. The rivals. -- Four men waiting -- The "longing to rise" -- The lure of politics -- "Plunder & conquest" -- The turbulent fifties -- The gathering storm -- Countdown to the nomination -- Showdown in Chicago -- "A man knows his own name" -- "An intensified crossword puzzle" -- "I am now public property" -- pt. 2. Master among men. -- "Mystic chords of memory" : Spring 1861 -- "The ball has opened" : Summer 1861 -- "I do not intend to be sacrificed" : Fall 1861 -- "My boy is gone" : Winter 1862 -- "He was simply out-generaled" : Spring 1862 -- "We are in the depths" : Summer 1862 -- "My word is out" : Fall 1862 -- "Fire in the rear" : Winter-Spring 1863 -- "The tycoon is in fine whack" : Summer 1863 -- "I feel trouble in the air" : Summer-Fall 1863 -- "Still in wild water" : Fall 1863 -- "There's a man in it!" : Winter-Spring 1864 -- "Atlanta is ours" : Summer-Fall 1864 -- "A sacred effort" : Winter 1864-1865 -- The final weeks : Spring 1865.
Includes bibliographical references and index.
Keywords: Lincoln, Abraham, -- 1809-1865.; Political leadership -- United States -- Case studies; Genius -- Case studies; Lincoln, Abraham, -- 1809-1865 -- Friends and associates; Presidents -- United States -- Biography; United States -- Politics and government -- 1861-1865.; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Amis et relations; Leadership politique -- v; v; z -- Biographies; x; Lincoln, Abraham -- (1809-1865) -- Amis et relations; Lincoln, Abraham -- (1809-1865).; Leadership politique -- y; x